SIKAP BAHASA SISWA KELAS VII A SMP NEGERI 3 MANDOR TERHADAP BAHASA INDONESIA - mulya karlina, elsa (Jurnal Ilmiah Edukatif, 2025)
The phenomenon that emerged in this study was the language attitudes of class VII A students at SMP Negeri 3 Mandor toward the use of Indonesian, both inside and outside the classroom. Although Indonesian is used formally in learning activities, students still tend to prefer using regional languages in daily interactions, especially outside the classroom. This study used a case study approach with 15 class VII A students and one language teacher as subjects. Data collection techniques included a questionnaire to measure students' cognitive, affective, and conative attitudes, as well as in-depth interviews to obtain an actual picture of Indonesian language use in daily interactions. Data were analyzed qualitatively through data reduction, presentation, and verification. The results showed that students' level of Indonesian language mastery and use was relatively low in both contexts. In the classroom, students often did not pay attention to spelling rules and standard sentence structures, appeared less enthusiastic in oral discussions, and tended to be passive when given speaking assignments. Outside the classroom, Indonesian language practice declined; students often communicated using a mixture of regional languages and slang in casual conversations. The influence of peer groups and informal communication habits were the main causes of this inconsistency